Contribution of Ophiocordyceps Sinensis (Berk.) Sung et Al. (Yarsa Gumba) in the Livelihood of Rural Communities in Kumaun Himalaya: Management and Conservation Issues - Pant, Girish Chandra; Tewari, Ashish (Indian Forester, 2014)
During summer collection of yarsa gumba, a highly priced natural product, is the main occupation of around 81% people of Munsyari Tehsil in Pithoragarh district of Uttarakhand resulting into collection of approximately 88.96 kg material worth ` 2.05 crore annually. It has completely changed the socio-economic set up of the region affecting the long-established agricultural and animal husbandry system too. The various issues pertaining to its collection have been discussed in details to suggest measures for the conservation and sustainable management of this valuable resource in the remotest part of the country.